The low-temperature specific heat of MWCNTs - Sumarokov, V.V.; Jeżowski, A.; Szewczyk, D.; Bagatski, M.I.; Barabashko, M.S.; Ponomarev, A.N.; Kuznetsov, V.L.; Moseenkov, S.I. (Физика низких температур, 2019)
The specific heat of multi-walled carbon nanotubes (MWCNTs) with a low defectiveness and with a low content of inorganic impurities has been measured in the temperature range from 1.8 to 275 K by the thermal relaxation method. The elemental composition and morphology of the MWCNTs were determined using scanning electron microscopy analysis and energy dispersion x-ray spectroscopy. The MWCNTs were prepared by chemical catalytic vapor deposition and have mean diameters from 7 nm up to 18 nm and lengths in some tens of microns. MWCNTs purity is over 99.4 at.%. The mass of the samples ranged from 2–4 mg. It was found that the temperature dependence of the specific heat of the MWCNTs differs significantly from other carbon materials (graphene, bundles of SWCNTs, graphite, diamond) at low temperatures. The specific heat of MWCNTs systematically decreases with increasing diameter of the tubes at low temperatures. The character of the temperature dependence of the specific heat of the MWCNTs with different diameters demonstrates the manifestation of different dimensions from 1D to 3D, depending on the temperature regions. The crossover temperatures are about 6 and 40 K. In the vicinity of these temperatures, a hysteresis is observed. Питому теплоємність багатостінних вуглецевих нанотрубок (БСВНТ) з низькою дефектністю та низьким вмістом неорганічних домішок виміряно в діапазоні температур 1,8–275 К методом теплової релаксації. Зразки БСВНТ отримано хімічним каталітичним осадженням з парової фази. Елементний склад і морфологію БСВНТ визначено за допомогою скануючої електронної мікроскопії та енергодисперсійної рентгенівської спектроскопії. Нанотрубки мали середній діаметр від 7 до 18 нм і довжину в кілька десятків мікрон. Чистота БСВНТ була більш ніж 99,4 ат.%. Маса зразків становила від 2 до 4 мг. Виявлено, що температурна залежність питомої теплоємності БСВНТ значно відрізняється від теплоємності інших вуглецевих матеріалів (графена, в’язок ОСВНТ, графіту, алмазу) при низьких температурах. Теплоємність БСВНТ систематично зменшується зі збільшенням діаметра нанотрубок при низьких температурах. Температурні залежності питомої теплоємності БСВНТ з різними діаметрами демонструють притаманний низьковимірним системам характер від 1D до 3D в залежності від температурних областей. Температури кросовера складають близько 6 та 40 К. Поблизу цих температур спостерігається гістерезис. Удельная теплоемкость многостенных углеродных нанотрубок (МСУНТ) с низкой дефектностью и низким содержанием неорганических примесей измерена в диапазоне температур 1,8–275 К методом тепловой релаксации. Образцы МСУНТ получены химическим каталитическим осаждением из паровой фазы. Элементный состав и морфология МСУНТ определены с помощью сканирующей электронной микроскопии и энергодисперсионной рентгеновской спектроскопии. Нанотрубки имели средний диаметр от 7 до 18 нм и длину в несколько десятков микрон. Чистота МСУНТ более 99,4 ат.%. Масса образцов составляла от 2 до 4 мг. Обнаружено, что температурная зависимость удельной теплоемкости МСУНТ значительно отличается от теплоемкости других углеродных материалов (графена, связок ОСУНТ, графита, алмаза) при низких температурах. Теплоемкость МСУНТ систематически уменьшается с увеличением диаметра нанотрубок при низких температурах. Температурные зависимости удельной теплоемкости МСУНТ с разными диаметрами демонстрируют присущий низкоразмерным системам характер от 1D до 3D в зависимости от температурных областей. Температуры кроссовера составляют около 6 и 40 К. Вблизи этих температур наблюдается гистерезис.